The Grammatical Term Interpreted By Another The Indefinite Term Interpreted As Definite As A Model/ المصطلح النحويّ المؤول بغيره النكرة المؤولة بمعرفة أنموذجا - Rusul Abdulrahim Turki; Dhafir Khairallah Jamil (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study addresses the issue of the intended indefinite noun (al-nakira al-maqsūda) in the chapter on vocative structures, as a precise grammatical model that deviates from the original declension of indefinite nouns—being constructed with the accusative case marker and treated as definite nouns in terms of grammatical ruling and function. The research aims to demonstrate that this departure cannot be correctly explained except on the basis of syntactic interpretation (al-taʾwīl), and that the intended indefinite noun is, in essence, an indefinite noun interpreted as definite. The study adopts a descriptive-analytical methodology based on tracking and surveying the statements of grammarians, then analyzing and discussing them in light of general grammatical rules. It concludes that the majority of grammarians, although they did not explicitly use the term